KAJIAN KELEMBAGAAN TERHADAP KEBERHASILAN KELOMPOK TANI HUTAN RAKYAT DI DESA DURJELA KECAMATAN PULAU-PULAU ARU KEPULAUAN ARU, MALUKU - Djelau, Ilya; Panjaitan, Poltak BP; Susdiyanti, Tun (Universitas Nusa Bangsa, 2014)
An institution has an important supporting role ini the management of forest community. In general the institutional system for forest community adopts aself-management. It has a certain degree of influence on its members’ compliance to its regulation. It is expented to be able to provide solution to the problems of farmers.This study was intended to examine the institutional system of forest community. The institutional system refers to such aspect as regulation, guides, forms of agreement, decision masking, value system, institutional capacity and knowingthe level of successthathas beenachievedbya groupof farmersin the Durjela villagecommunity forest management. These results indicate that institutional forest farmer groups in the Durjela village formed from assistance programs and community desires. Institutional system Durjela Village farmer groups in the form of an agreement that is made of non-formal, Guidelines rooted in religion and local wisdom, decision making by consensus, the value system is characterized by the perception of the essence of life is good, working to make ends meet, oriented to future, the success of Durjela Village farmer groups included in the rate was due to the structural aspects, aspects of membership in the institutional and cultural aspects have not been entirely successful.